Abilities of Village Health Volunteers in Determining Drug Related Problems for Diabetes and Hypertension Patients - Parina Na Pathalung; Phayong Thepaksorn (Intelektual Pustaka Media Utama, 2017)
The objective of this study was to assess the Village Health Volunteers (VHVs) on their knowledge and skills for determining drug-related problems (DRPs) for hypertension (HTN) and diabetes (DM) patients. This study was conducted among 36 VHVs between March and October, 2014 in ten districts of Trang Province. The semi-structured questionnaire interviews and tests have been developed according to knowledge and skills based health determinants for DRPs. The DRPs training program was assigned including, 1) a short course training (2-day) and hands-on training (1-week) followed up, 2) field work for determining DRPs (16-week) and 3) an assessment for determining DRPs in knowledge and competent skills. All completed data of 25 female VHVs were analyzed with age of 42.93 years old on average. About 68% were age higher than 40 years old and most of them were Para rubber farmers (76%). Most of them had a primary education level (60%) and almost a half had more than ten years in VHVs’ service (n =12; 48%). Their knowledge scores for determining DRPs were 12.88 on average, in total of 15 points. Their overall scores for skills presented were 35.48 out of 50 points in total. In conclusion, this program can enhance VHVs’ abilities for determining DRPs for HTN and DM patients. Our findings may contribute to future development of VHVs program for improving VHVs competent skills for DRPs chronic diseases.